2017
DOI: 10.11646/zootaxa.4337.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Description of the helminth communities of sympatric rodents (Muroidea: Cricetidae) from the Atlantic Forest in northeastern Argentina

Abstract: Taxonomic and ecological aspects of the helminths found in the assemblage of sigmodontine rodents (Cricetidae-Muroidea) of the Atlantic Forest in Argentina are studied in this paper. The following species Akodon montensis, Brucepattersonius sp. and Thaptomys nigrita (Tribe Akodontini), as well as, Euryoryzomys russatus, Nectomys squamipes, Oligoryzomys nigripes, and Sooretamys angouya (Tribe Oryzomyini) are analyzed. A complete taxonomic list with a total of 25 species of helminths, including Digenea (Dicrocoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 522 publications
(47 citation statements)
references
References 0 publications
6
32
1
8
Order By: Relevance
“…The highest total helminth species richness in A. montensis (six) in comparison with other rodents corroborates the results from other surveys which also found greater richness in this host (PÜTTKER et al, 2008;PANISSE et al, 2017). However, the total helminth species richness found for this rodent was lower than those reported in other studies; Püttker et al (2008) observed seven morphotypes in a study in the State of São Paulo, Brazil; Panisse et al (2017) reported eight helminth species for this rodent in Misiones Province, Argentina. In a previous study carried out in a different locality in PARNASO (Teresópolis) and in forest fragments on its surroundings, Simões et al (2011) reported twelve helminth species in A. montensis, considering 13 localities.…”
Section: Rodent Helminth Faunasupporting
confidence: 87%
See 4 more Smart Citations
“…The highest total helminth species richness in A. montensis (six) in comparison with other rodents corroborates the results from other surveys which also found greater richness in this host (PÜTTKER et al, 2008;PANISSE et al, 2017). However, the total helminth species richness found for this rodent was lower than those reported in other studies; Püttker et al (2008) observed seven morphotypes in a study in the State of São Paulo, Brazil; Panisse et al (2017) reported eight helminth species for this rodent in Misiones Province, Argentina. In a previous study carried out in a different locality in PARNASO (Teresópolis) and in forest fragments on its surroundings, Simões et al (2011) reported twelve helminth species in A. montensis, considering 13 localities.…”
Section: Rodent Helminth Faunasupporting
confidence: 87%
“…These authors reported the occurrence of a new species of the genus Stilestrongylus in Argentina. In the present study, the only specimen of Stilestrongylus found in T. nigrita seems to be the same species that was found by Panisse et al (2017) based on the morphological characteristic observed. However, the authors did not provide further information.…”
Section: Rodent Helminth Faunasupporting
confidence: 73%
See 3 more Smart Citations